Entrepreneurial Skills for Operational Adaptation to Emerging Trends in the Electrical Industry - Yusuf, Mohammed Adamu; Ibanga, Isaac John (Journal of Novel Engineering Science and Technology, 2023)
The study's primary purpose was to assess the entrepreneurial skills required by electrical engineering students for operational adaptation to emerging trends in the Electrical Industry in Nigeria. The study, which adopted a descriptive survey research design, was conducted in northeast Nigeria and had three research questions and three null hypotheses. The study population was 211, which comprised 178 Lecturers of electrical/electronics from the three Federal Universities and seven polytechnics offering electrical/electronics engineering and 49 electrical/electronics industry supervisors in 33 establishments in North Eastern Nigeria. The study adopted a purposive sampling technique in which the entire population was used as the sample for the analysis. A structured questionnaire developed by the researcher titled Questionnaire for Entrepreneurial Skills Required by Electrical Engineering Students for Operational Adaptation to Emerging Trends (QESTREESOAET) was used as an instrument for data collection. Three experts validated the instrument, and a reliability index of 0.89 was obtained using Cronbach Alpha. The mean statistic was used to answer the research questions, while the t-test was used to test the null hypotheses at a 0.05 significance level. The study's findings revealed that ten managerial, ten accounting and 18 marketing entrepreneurial skills were identified as necessary skills for operational adaptation to emerging trends in the Electrical Industry in Nigeria. Based on the findings, the study recommended that the National University Commission (NUC), National Board for Technical Education (BTE) and the National Commission for Colleges of Education (NCCE) should develop a curriculum that will adequately introduce the concept of management and its importance to the students for adequate assimilation and practice for all students of electrical engineering.